In vitro plant regenaration of tobacco (nicotiana tabaccum TAPM 26) - Kaya, Yilmaz (2010)
In the present research, a reproducible procedure has been developed for efficient plant regeneration of shoot from cotyledon explants of Nicotiana tabaccum TAPM 26. In vitro regeneration of Nicotiana tabaccum TAPM 26 was efficiently achieved applying combination of growth hormones supplemented into MS medium using cotyledon from 5-day-old and 7-day-old as explants. The growth hormones used were IAA for auxin (0.0, 0.1, 1, 10 mgL-1) and BAP for cytokinin (0.0, 0.1, 1, 10 mgL-1 ). The effects of growth hormones combination were assessed based on number of shoot and roots formation. Maximum number of shoots produced per explant was found when media continued with 10 µM BAP +0.0 µM IAA after 4 weeks in culture. Maximum number of root produced per explant was reached when media continued 10 µM IAA after 4 weeks in MS media. The current techniques proved that Nicotiana tabaccum was successfully propagated by direct organogenesis and can be applied for further research in making as transgenic Nicotiana tabaccum.